(untitled) - Miller, Judy L. (White Plains, N.Y, 2017)
The series also encourages students to discuss and write about the ideas they discovered in the readings, making them better speakers and writers of English as well.
Keywords: Reading comprehension,Đọc hiểu; Câu hỏi và bài tập